The effect of antiretroviral therapy on the oral and periodontal status of patients with hiv/aids: narrative review - Grueso, Lorena; Soto, Jorge; Amaya, Sandra; Pacheco, Olga Isabel (Revista Estomatología, 2024)
Patients with HIV have a decrease in CD4+ T cells, making them more susceptible to developing infections. Antiretroviral therapy (ART) decreases viral load and improves T-CD4 production. It has been suggested that periodontitis could decrease its prevalence due to the use of antiretrovirals. Objective: To identify, through a literature review, the most recent and relevant evidence of patients with HIV and the effect of ART on oral and periodontal status. Materials and Methods: A search for clinical articles was carried out in PubMed, Science Direct LILACS and Google Scholar, between the years 2011 and 2023. Selection criteria: patients with ART for HIV and evaluation of oral/periodontal status. Clinical trials, systematic reviews and meta-analyses were included. Results: Initially, 173 articles were identified, 135 were excluded, finding in the end only two systematic reviews and no clinical trials. One systematic review presented 18 articles with 1632 adult patients with periodontal disease (PD) and highly active antiretroviral therapy (HAART) and the other in children with 12 articles and 1002 patients <18 years of age reviewing periodontal status and oral lesions. Conclusion: HAART reduces the prevalence of oral manifestations in children with HIV; but not so with PD in adult patients with HAART, with the exception of necrotizing gingivitis.